A holistic approach to the evaluation of the indoor temperature based on thermal comfort and learning performance. (June 2021) - Jiang, Jing; Wang, Dengjia; Liu, Yanfeng; Di, Yuhui; Liu, Jiaping
Abstract: Indicators and methods in current thermal comfort evaluation models are based on the average level for entirely society, which is difficult to use to a direct guide for the design of classroom thermal environments in primary and secondary schools. The determination of indoor parameters is mainly based on a single thermal comfort index, with little consideration of the impact of thermal environment on learning performance, and combinations of both considerations is even rarer. The quantitative relationship between temperature and thermal comfort was established, with percentage of satisfied as a thermal comfort evaluation index. The quantitative relationships among percentage of qualified, performance index, and temperature were established with the group's percentage of qualified was proposed to characterize learning performance. Therefore, a method for determining the temperature design parameters of the classroom was proposed, taking into consideration the comprehensive effects of thermal comfort and learning performance. Temperature ranges of different thermal comfort and learning performance levels were recommended. The upper limit of the recommended temperature with higher comfort and learning performance was 5 °C lower than the low limits of international standards, which could effectively reduce energy consumption of school buildings in winter, and provide a theoretical basis for improvement of classroom environment design. Highlights: The temperature parameter should consider thermal comfort and learning performance. Percentage of qualified was proposed to characterize the group' learning performance. Theory of spatial analysis was introduced to design thermal environment parameter. Quantitative relationship between temperature and thermal comfort was established. Quantitative relationship between temperature and learning performance was set up.